The Psychological Value in the Poetry “Bukit Doa” by Irna Novia Darmayanti - Hidayat Nur Septiadi; Yuni Endah Pratiwi; Rahmad Rafid (Journal Corner of Education, Linguistics, and Literature, 2021)
A literary work cannot be separated from the psychology of the character and the author. It has become the basis of a literary work. This study discusses the psychological value pioneered by Abraham Maslow, who tends to analyze the value of Literary Psychology in terms of a person's needs. This research aims to describe and explain the psychology of literature in verse “Bukit Doa” written by Irna Novia Damayanti. The method used in this research is qualitative research by describing and explaining words related to the character's psychology. The results obtained from this study are, the psychological or psychological value received by the character is psychology caused by the emergence of several needs of a person, this includes the need for a sense of security and peace, as well as love and love, which support religious needs (Spiritual).